2014
DOI: 10.1186/s13075-014-0450-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of cerebrospinal fluid anti-Sm antibodies with acute confusional state in systemic lupus erythematosus

Abstract: IntroductionNeuropsychiatric manifestation in systemic lupus erythematosus (NPSLE) is one of the most serious complications of the disease. Previous studies revealed the strong association between serum anti-Sm and organic brain syndrome, consisting mainly of acute confusional state (ACS) of diffuse psychiatric/neuropsychological syndromes (diffuse NPSLE). However, the precise mechanism by which anti-Sm causes diffuse NPSLE remains unclear. Of note, recent studies demonstrated that anti-U1 RNP antibodies (anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“…As is consistent with previous studies [5], Q albumin values were significantly elevated in diffuse NPSLE (8.87 ± 6.96) compared with in focal NPSLE (4.74 ± 2.81) (p ¼ 0.033) (Figure 3, left). There were no significant differences in CSF C5a or in serum C5a between diffuse NPSLE and focal NPSLE (Figure 3, middle and right).…”
Section: Relationship Between Bbb Integrity and C5a In Npslesupporting
confidence: 93%
See 2 more Smart Citations
“…As is consistent with previous studies [5], Q albumin values were significantly elevated in diffuse NPSLE (8.87 ± 6.96) compared with in focal NPSLE (4.74 ± 2.81) (p ¼ 0.033) (Figure 3, left). There were no significant differences in CSF C5a or in serum C5a between diffuse NPSLE and focal NPSLE (Figure 3, middle and right).…”
Section: Relationship Between Bbb Integrity and C5a In Npslesupporting
confidence: 93%
“…It is therefore suggested that C5a might be involved in BBB damages in human SLE. Of note, we have recently disclosed that anti-Sm antibodies and anti-NR2 antibodies play important roles in acute confusional state (ACS), the severest form of diffuse NPSLE [4,5]. More importantly, the elevation of these antibodies in CSF was shown to result mainly from BBB damages rather than the increased production in CNS [4,28].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been associated with the presence of anti-NR2 antibodies and anti-Sm antibodies in the CSF 10,28 . The pathogenic mechanism behind this diffuse neuropsychiatric manifestation seems to be primarily inflammatory with increased production of inflammatory mediators, BBB disruption, and intrathecal immune complex formation 6 .…”
Section: Acute Confusional Statementioning
confidence: 99%
“…Potential pathogenic mechanisms in primary NPSLE are direct action of intrathecal inflammatory cytokines, blood-brain barrier (BBB) disruption, accelerated atherosclerosis and thrombotic vasculopathy caused by aPL antibodies 4 . Autoantibodies may also bind to neurons leading to neuronal dysfunction and apoptosis 7,10 (Table 2).…”
Section: Neuropsychiatric Systemic Lupus Erytematosusmentioning
confidence: 99%